Waste Scavenging and Its Contribution for Survival and Urban Recycling in Kota Kinabalu City, Sabah, Malaysia - Mohammad Tahir Mapa; Jane C Powell; Abdul Hair Beddu Asis; Nordin Sakke; Aliakbar Gulasan (Faculty of Geography UGM and Indonesian Geographers Association, 2019)
High generation of solid waste has been identified as one factor contributing to the world’s environmental problems. The decrease in suitable landfill sites and scarcity of natural resources is creating greater demand for remanufacturing and reuse. This study aims to examine the contribution and issues embedded in scavengers’ group to achieved high rate of recycling in waste management program. In order to answer the research objective, this research utilized in-depth interviews conducted with scavengers’ group. This study revealed scavenging activity is an important element in waste management with positive impact on the economic and environment. Therefore, to support this, the scavengers group need to be part of the government’s attempt to realise its recycling objectives.